KELAYAKAN INVESTASI DAN RISIKO PENGEMBANGAN UNIT DIALISIS RSU BIDADARI BINJAI - Icha Prasetina; Erliany Syaodih; Maxsi Ary (LPPM Universitas Adhirajasa Reswara Sanjaya, 2026)
The growing need for dialysis therapy requires hospitals to expand service capacity while maintaining financial sustainability and operational safety. Bidadari Binjai General Hospital faces limitations in dialysis machines and service space, while utilization of the Dialysis Unit remains high, making a measured investment decision necessary. This study aims to analyze the feasibility of investing in the development of the Dialysis Unit and to identify risks that may affect investment sustainability. A mixed-methods case study approach was applied. Quantitative analysis used financial data and the Payback Period, Net Present Value, and Internal Rate of Return methods, while qualitative analysis used interviews, observation, documentation, triangulation, and risk mapping based on Enterprise Risk Management. The findings indicate that the proposed development of the Dialysis Unit is financially feasible, with a relatively rapid investment recovery and positive economic value. Nevertheless, investment sustainability is affected by risks related to delayed payer claims, changes in reimbursement regulations, water-treatment system failures, clinical incidents, and shortages of skilled personnel. The novelty of this study lies in integrating capital-budgeting analysis with a hospital operational risk matrix as a basis for investment decisions. This approach confirms that service-development decisions should not rely solely on financial indicators but must also incorporate structured risk mitigation. Kebutuhan terapi dialisis yang terus meningkat menuntut rumah sakit memperluas kapasitas layanan dengan tetap menjaga keberlanjutan keuangan dan keselamatan operasional. RSU Bidadari Binjai menghadapi keterbatasan mesin dan ruang pelayanan, sementara utilisasi Unit Dialisis terus tinggi sehingga diperlukan keputusan investasi yang terukur. Penelitian ini bertujuan menganalisis kelayakan investasi pengembangan Unit Dialisis sekaligus mengidentifikasi risiko yang dapat memengaruhi keberlanjutan investasi. Penelitian menggunakan pendekatan mixed methods dengan studi kasus. Analisis kuantitatif dilakukan terhadap data keuangan menggunakan Payback Period, Net Present Value, dan Internal Rate of Return, sedangkan analisis kualitatif memanfaatkan wawancara, observasi, dokumentasi, triangulasi, serta pemetaan risiko berbasis Enterprise Risk Management. Hasil penelitian menunjukkan bahwa rencana pengembangan Unit Dialisis layak secara finansial, dengan pengembalian investasi yang relatif cepat dan nilai investasi yang memberikan manfaat ekonomi positif. Namun, keberlanjutan investasi dipengaruhi oleh risiko keterlambatan klaim penjamin, perubahan regulasi tarif, gangguan sistem pengolahan air, risiko klinis, serta keterbatasan tenaga terampil. Kebaruan penelitian terletak pada integrasi analisis capital budgeting dengan matriks risiko operasional rumah sakit sebagai dasar keputusan investasi. Pendekatan ini menegaskan bahwa keputusan pengembangan layanan tidak cukup ditentukan oleh indikator finansial, tetapi juga memerlukan mitigasi risiko yang terstruktur.